La Flora for flute (doubling alto flute), clarinet, percussion, violin, and cello - Singleton, Alvin 1940- (Schott, 2014)
In one movement. Commissioned by Orchestra of Our Time, Inc. Premiered in New York, October 1983. The music was inspired by the figure of the goddess Flora in a painting by Botticelli. Of advanced difficulty